Pendekatan, Metode, dan Peran Filsafat Pendidikan Islam - Maria Ulfah Ashar; Marjuni M; Andi Achruh Pasinringi (Madani: Jurnal Ilmiah Multidisiplin, 2026)
Islamic Educational Philosophy serves as an epistemological foundation for developing an educational system that promotes the holistic development of human beings by integrating intellectual, spiritual, moral, and social dimensions. This article aims to analyze the approaches, methods of development, and strategic roles of Islamic Educational Philosophy in addressing contemporary educational challenges characterized by value crises, the secularization of knowledge, and technological disruption. This study employs a library research method using a descriptive-analytical approach to examine relevant and recent scholarly literature. The findings reveal that Islamic Educational Philosophy is developed through four major approaches: theological (naqli), philosophical (aqli), historical-sociological, and integrative-interconnective, which complement one another in constructing a tawhid-based educational paradigm. Its development is further supported by speculative-contemplative, normative, descriptive-analytical, and hermeneutical methods that integrate religious texts, contextual understanding, and empirical realities. Strategically, Islamic Educational Philosophy functions as a source of inspiration for formulating educational objectives, a critical framework for evaluating secular educational paradigms, an evaluative tool for educational practices, and an integrative bridge between religious and general sciences. Therefore, Islamic Educational Philosophy remains highly relevant in fostering insan kamil (the complete human being), characterized by strong moral values, intellectual competence, spiritual awareness, and the ability to respond to global challenges while preserving Islamic values.